Solve for h -15h=16h+6

Math
-15h=16h+6
Move all terms containing h to the left side of the equation.
Tap for more steps…
Subtract 16h from both sides of the equation.
-15h-16h=6
Subtract 16h from -15h.
-31h=6
-31h=6
Divide each term by -31 and simplify.
Tap for more steps…
Divide each term in -31h=6 by -31.
-31h-31=6-31
Cancel the common factor of -31.
Tap for more steps…
Cancel the common factor.
-31h-31=6-31
Divide h by 1.
h=6-31
h=6-31
Move the negative in front of the fraction.
h=-631
h=-631
The result can be shown in multiple forms.
Exact Form:
h=-631
Decimal Form:
h=-0.19354838…
Solve for h -15h=16h+6

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top